A prospective cohort study protocol: monitoring and surveillance of adverse events following heterologous booster doses of Oxford AstraZeneca COVID-19 vaccine in previous recipients of two doses of Sinopharm or Sputnik V vaccines in Iran - Shahin Soltani; Behzad Karami Matin; Mohammad Mehdi Gouya; Sayed Mohsen Zahraei; Ghobad Moradi; Omid Chehri; Moslem Soofi; Mehdi Moradinazar; Fatemeh Khosravi Shadmani; Mahsa Kalantari; Hamidreza Khajeha; Mohammad Hassan Emamian; et al. (BMC, 2023)
Abstract Background Regarding the paucity of evidence on the side effects of the booster dose of Oxford AstraZeneca vaccine in vaccinated people with Sinopharm or Sputnik V, we aimed to set up a cohort event monitoring (CEM) study to capture adverse events occurring in individuals who will receive the booster doses of AstraZeneca (either the first or second booster dose) following being vaccinated with Sinopharm or sputnik V vaccines in Iran. Methods The present study is an active COVID-19 vaccine safety surveillance through an observational prospective cohort study that will be conducted in vaccination centers in Iran. The study will be conducted in twelve provinces of Iran. Study sites are vaccination centers where the AstraZeneca vaccine is administered to the cohort population. The study population includes all individuals who have received two doses of Sinopharm or Sputnik V vaccines and either the first or second booster dose of AstraZeneca according to the national guidelines for immunization in Iran in 2023. We are planning to include 30,000 eligible people in this study. Each individual will be followed up for 13 weeks after either the first or second booster dose of the AstraZeneca vaccine. Furthermore, convenience sampling is used to include participants in the present study. Participation in the study will be strictly voluntary. Discussion With the planned study we will provide a valid epidemiological evidence to improve the understanding of the safety of the booster dose of the AstraZeneca and to better evaluate the effectiveness of public health interventions. This could help policy makers in managing the COVID-19 pandemic according to scientific evidence.